Rapid synthesis of novel isoindolo[1,2-a]quinazoline on ionic liquid support under microwave irradiation - Jedhe Ramchandra; Paike Vijaykumar; Sun Chung-Ming (Green Processing and Synthesis, 2013)
An efficient ionic liquid-supported (ILs) strategy is applied for the synthesis of substituted isoindolo[1,2-a]quinazoline under microwave irradiation. The ILs enhances the coupling capability of microwave flash heating in green organic synthesis. The acid-catalyzed heterocyclization of ionic liquid bounded 3-amino-4-[(alkylamino)methyl]benzoate was carried out with α-ketobenzoic acids or γ-ketoaliphatic acid to synthesize five and six member fused N-heterocycles. The one-pot heterocyclization proceeded via amidation between primary amines and 2-acylbenzoic acids or γ-ketoaliphatic acid, followed by the intramolecular dehydrocyclization with the keto group under microwave heating. The significant advantages in green synthesis by using ILs synthesis under controlled microwave dielectric heating are the dramatic reduction in reaction time, improved energy utilization, simple purification, and increasing the productivity of desired compounds.